Association of Interleukin-10 Methylation Levels With Gestational Diabetes in a Taiwanese Population - Kang, Jessica; Lee, Chien-Nan; Li, Hung-Yuan; Hsu, Kai-Han; Wang, Shu-Huei; Lin, Shin-Yu (Frontiers in Genetics, 2018)
Objective: Gestational diabetes mellitus (GDM) is defined as glucose intolerance with onset during pregnancy, which is also associated with future metabolic diseases in both patients and their offspring. The mechanisms underlying this condition remain largely unknown and may be partly related to epigenetics. The aim of this study was to compare the methylation levels of the cytokine interleukin-10 (IL-10) in pregnant women and their fetuses under both hyperglycemic and euglycemic environments, as those levels may be a clue to the epigenetic mechanisms underlying pathogenesis of GDM. Methods: We analyzed the methylation levels of the IL-10 gene in maternal blood, cord blood, and placental tissue in both a GDM group (n = 8) and a control group (n = 24) using a LightCycler LC480 (Roche, Rotkreuz, Switzerland). IL-10 concentrations in maternal blood and THP-1 cells were measured by enzyme-linked immunosorbent assay (ELISA) using BD OptEIA Human IL-10 ELISA kits (BD Biosciences Pharmingen, San Diego, CA, United States). Results: The maternal blood IL-10 methylation levels in the GDM group and the control group were 0.23 ± 0.04 and 0.26 ± 0.04, respectively (p = 0.03), but there were no significant differences between the levels of the two groups in the cord blood or placental tissue. Increased IL-10 plasma concentrations were discovered under hyperglycemic environments and were confirmed via the THP-1 cell line. Conclusion: Hypomethylation of maternal blood and increased plasma IL-10 concentrations before birth were found in the GDM group.